Real-time load flow program for the PSSL power system simulator - Manimtim, James Rene S.
Real-Time Load Flow is an analytical tool that helps power system engineers make decisions to ensure the safe and proper operation of a power system. Load flow analysis is used to simulate power systems. Real-time load flow is used to monitor the current state of an actual power system. To augment the educational value of the Power System Simulator of the UP PSSL (Power System Simulation Lab), a real-time load flow program was developed, The real-time load flow program implements the Super Decoupled Load Flow Algorithm proposed by Haley and Ayres (1985) ['Super Decoupled Load Flow with Distributed Slack Bus' IEEE Trans., 1985; PAS-104, (1), pp. 104-111]. The program receives data inputs from a SCADA system. The program was tested on a five-bus transmission system model with installed intelligent electronic devices (IEDs). Tests results show an accurate load flow program which can be used for real-time and event simulation purposes.